Three new species and additional records of Lobrathium Mulsant & Rey (Coleoptera: Staphylinidae: Paederinae) from China - Huang, Lei; Xiong, Zi-Chun; Da, Wa; Peng, Zhong (Zootaxa, 2026)
Material of the genus Lobrathium Mulsant & Rey, 1878 from the Chinese provinces of Zhejiang, Jiangxi, Hubei, Hunan, Guangdong, Guangxi, Chongqing, Guizhou, Yunnan, Xizang, Shaanxi and Gansu is examined. Eleven species were identified, eight of them described previously and three are newly described: L. gai Huang & Peng, sp. nov. (Gansu: Dangchang County), L. medogense Huang & Peng, sp. nov. (Xizang: Mêdog County), and L. xiang Huang & Peng, sp. nov. (Yunnan: Yun County). New provincial records are provided for L. bispinosum Assing, 2012 from Guangxi and for L. duplex Assing, 2012 from Xizang. Including the new taxa, 71 Lobrathium species are currently known from China.